THE INFLUENCE OF WORK CULTURE, MOTIVATION AND COMPENSATION TO THE PERFOMANCE OF EMPLOYEES IN GOVERNMENT - Sulaeman, Maman; Marlina, Lina; Yuliani, Gina Nur (eBA Journal: Journal Economics, Bussines and Accounting, 2018)
The purpose of this study were to determine the effect of work culture, motivation and compensation to employee performance, to analyze the influence of corporate culture, motivation and compensation to employee performance. The object to be studied is the WTO (the regional organizations), which includes Office, the Environment Agency and the Office in the City of Tasikmalaya. The method used is descriptive method with survey method. The collection of data obtained by questionnaires, interviews, and literature. The population in this study is a civil servant at the Department, the Environment Agency and the office in the City of Tasikmalaya. By using path analysis, the results of this study showed that partially, workplace culture, motivation and compensation have a significant influence on employee performance. Simultaneously, work culture, motivation and compensation have a significant influence on employee performance, so the hypothesis is verified. This means that the work culture, motivation and compensation significantly influence employee performance.